Acta Horticulturae: Promusa-ISHS proceedings: Global Perspectives on Asian Challenges - Bergh, Inge van den; Smith, M.; Swennen, Rony L.; Hernanto, C. (2011)
This book is the sum of 73 peer-reviewed papers presented during the International ISHS-ProMusa Symposium on Global Perspectives on Asian Challenges.